GPR11, a Putative Seven-Transmembrane G Protein-Coupled Receptor, Controls Zoospore Development and Virulence of Phytophthora sojae - Wang, Yonglin (American Society for Microbiology, 2010)

(untitled)
G protein-coupled receptors (GPCRs) represent a large receptor family involved in a broad spectrum of cell signaling. To understand signaling mechanisms mediated by GPCRs in Phytophthora sojae, we identified and characterized the PsGPR11 gene, which encodes a putative seven-transmembrane GPCR. An expression analysis revealed that PsGPR11 was differentially expressed during asexual development. The highest expression level occurred in zoospores and was upregulated during early infection. PsGPR11-deficienct transformants were obtained by gene silencing strategies. Silenced transformants exhibited no differences in hyphal growth or morphology, sporangium production or size, or mating behavior. However, the release of zoospores from sporangia was severely impaired in the silenced transformants, and about 50% of the sporangia did not completely release their zoospores. Zoospore encystment and germination were also impaired, and zoospores of the transformants lost their pathogenicity to soybean. In addition, no interaction was observed between PsGPR11 and PsGPA1 with a conventional yeast two-hybrid assay, and the transcriptional levels of some genes which were identified as being negatively regulated by PsGPA1 were not clearly altered in PsGPR11-silenced mutants. These results suggest that PsGPR11-mediated signaling controls P. sojae zoospore development and virulence through the pathways independent of G protein.